Effect of Vitamin D Status on Vascular Function of the Aorta in a Rat Model of PCOS. (19th March 2021) - Lajtai, K.; Tarszabó, R.; Bányai, B.; Péterffy, B.; Gerszi, D.; Ruisanchez, É.; Sziva, R. E.; Korsós-Novák, Á.; Benkő, R.; Hadjadj, L.; Benyó, Z.; Horváth, E. M.; et al.
Abstract : Polycystic ovary syndrome (PCOS) is associated with elevated cardiovascular risk. Early vascular dysfunction may lead to the development of cardiovascular disease in PCOS. Vitamin D deficiency (VDD) is a common comorbidity of PCOS that contributes to the pathogenesis of the disease and its complications. Both PCOS and VDD are accompanied by increased oxidative stress that may be involved in the arising vascular dysfunction. We aimed to investigate the role of vitamin D status on aortic function. PCOS was induced by an 8-week-long transdermal testosterone treatment of female rats, and low and adequate vitamin D status was achieved by dietary means. Contraction and relaxation abilities of isolated aortic segments were measured by myograph. Resorcin-fuchsin staining and immunohistochemical labeling of 3-nitrotyrosine were performed. No difference was shown in the norepinephrine-induced contraction of the aortas of different groups, whereas we detected reduced acetylcholine- and insulin-evoked relaxation in VDD groups. A lower level of resorcin-fuchsin staining and elevated 3-nitrotyrosine immunostaining was observed in VDD. In our study, we demonstrated early endothelial dysfunction in VDD PCOS rat model. Vitamin D supplementation could prevent vascular disturbances, while VDD itself damaged endothelium-dependent vasorelaxation and induced nitrative stress.